Noble Character Building at Widya Kusuma Islamic Kindergarten, Saladara, Cirebon, Indonesia - Ahmad Ridwan, Wawan; Rindanah, Rina; Dumilah, Ratna; Leti, Gratia; Yusup, Muhammad (Annpublisher, 2024)
Prophet Muhammad was given the task of forming akhlakul karimah by Muslims. The next generation will be strong and resilient if they have noble character. Character-building programs are the most critical need in Indonesia ahead of Indonesia Emas 2045. The basis of character education in the Islamic perspective is the holy book of the Qur'an and the Hadith of the Prophet. The Qur'an is the basis of all areas of life, including moral matters. The character-building program at Widya Kusuma Saladara Islamic Kindergarten includes three successes, six noble phobias, four ropes of faith, three principles of cooperation, four maqodirulloh, four spinning wheels, and five conditions of harmony and compactness. This program is instilled from an early age, from kindergarten to early childhood education, so that akhlakul karimah will be formed in adolescence and adulthood and ready to become future leaders.